Dynamic analysis of tramcar suspension system - Mohamed Rehan, Muhammad Saifuddin (2006)
Suspension system plays an important role in the performance of a vehicle, especially the vehicle handling and ride comfort. The objective of this project is to analyse the passenger ride comfort of a tramcar manufactured by UTM. Numerical analysis was performed on the tramcar suspension system, where the system was modelled and simulated. A full car model was successfully developed, and validated using available experimental data from the work published by other researcher. MATLAB Simulink software was used to simulate the system and obtain the system response. The comfort level was evaluated based on the displacement and acceleration response, considering the bouncing, pitching and rolling factors. The simulation results for tramcar suspension system were then evaluated by comparing them with simulation results for Proton Waja 1.6 and available standards. Based on the evaluation, the conclusion on the tramcar ride comfort was made. It was concluded that the tramcar ride comfort is comparable to the ride comfort of a Proton Waja, and is at an acceptable level. The role of suspension spring stiffness in relation to ride quality was also analysed. From the suspension parameter analysis, it was concluded that the ride comfort of the tramcar can be improved to an optimum level by having the lowest practical spring stiffness value. The tramcar suspension spring stiffness was said to be already in the region of the lowest practical value in the sense of avoiding a very low natural frequency assimilated to motion sickness. Some suggestions have been made at the end of the report for possible improvement or extension to this study.